FUNGSI DAN MAKNA KOTOWAZA KATA HEWAN PADA MANGA DORAEMON NO KOTOWAZA JITEN - Yanti, Ni Nyoman Erena; Nurita, Wayan; Andriyani, Anak Agung Dian (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2022)
This article describes the function and meaning of the animal word kotowaza contained in Doraemon no Kotowaza Jiten's kotowaza. The writing of this article uses a qualitative descriptive method. The related functions in this article are expressive functions, namely functions regarding attitudes and emotions, referential functions, namely functions regarding surrounding objects, and poetic functions, namely functions that express the contents of thoughts and feelings. Meanwhile, the related meaning of kotowaza is the lexical meaning, namely the meaning according to the dictionary, the meaning of the proverb is the predicted meaning because of the association of the lexical meaning and the denotative meaning is the basic meaning or the actual meaning.